2012
DOI: 10.1038/ajh.2012.76
|View full text |Cite
|
Sign up to set email alerts
|

Automated Office Blood Pressure is Associated with Urine Albumin Excretion in Hypertensive Subjects

Abstract: In this study, microalbuminuria correlated similarly with high-quality AOBP and ABP readings, further supporting the use of AOBP in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
2
12
0
2
Order By: Relevance
“…Mean AOBP was 129/79 mm Hg compared with a mean daytime ABPM of 128/79 mm Hg, whereas oscillometric result was 134/84 mm Hg and the auscultatory result was 132/83 mm Hg, suggesting that AOBP is a more accurate technique than conventional office measurements in the evaluation of an individual's true BP status. Our findings concur with previous results showing similar values for mean AOBP and daytime ABPM, with both values being significantly lower than conventional office readings; this also suggests that white coat hypertension was significantly more prevalent when routine OBP readings were analyzed 6, 8, 16, 17. Staessen et al reviewed 30 studies in which conventional office readings were compared with daytime ABPM in untreated patients with borderline or definite hypertension; their findings showed that mean OBP was 12/2 and 20/1 mm Hg higher, respectively, than the corresponding mean daytime ABPM 18.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mean AOBP was 129/79 mm Hg compared with a mean daytime ABPM of 128/79 mm Hg, whereas oscillometric result was 134/84 mm Hg and the auscultatory result was 132/83 mm Hg, suggesting that AOBP is a more accurate technique than conventional office measurements in the evaluation of an individual's true BP status. Our findings concur with previous results showing similar values for mean AOBP and daytime ABPM, with both values being significantly lower than conventional office readings; this also suggests that white coat hypertension was significantly more prevalent when routine OBP readings were analyzed 6, 8, 16, 17. Staessen et al reviewed 30 studies in which conventional office readings were compared with daytime ABPM in untreated patients with borderline or definite hypertension; their findings showed that mean OBP was 12/2 and 20/1 mm Hg higher, respectively, than the corresponding mean daytime ABPM 18.…”
Section: Discussionsupporting
confidence: 92%
“…4,5 Furthermore, both AOBP and daytime ambulatory BP have been shown to correlate better with left ventricular mass, microalbuminuria, and intima-media thickness of the carotid artery than conventional clinical readings. [6][7][8] In addition to SPRINT, AOBP has also been used for cardiovascular outcomes in a Canadian study of older community-dwelling people followed up for an average of 4.6 years. In this study, AOBP values of 110 to 119 mm Hg were associated with lower cardiovascular risk.…”
mentioning
confidence: 99%
“…1,4 This association is particularly evident for patients with chronic kidney disease [19][20][21] and patients with resistant hypertension. 13,14,[22][23][24] Although in most of these studies such a correlation has been shown to be quite strong with 24-hour ambulatory BP but weaker with routine office BP, [16][17][18]22,23 2 recently published small studies reported similar correlations of microalbuminuria with either high-quality automated office BP 25 or community pharmacy BP and 24-hour ambulatory BP 26 readings. However, there is scarce information about this association for values of UAE below the lower cutoff used for the definition of microalbuminuria.…”
Section: Discussionmentioning
confidence: 62%
“…Automated office BP measurement (AOBP) has been proven to correlate well with ABPM . There is also some evidence of a correlation with end‐organ damage . Observer error is eliminated and WCE is greatly reduced if measurement is performed with an observer absent, in an uninterrupted private space.…”
Section: Characteristics Of Common Methods Of Bp Measurementmentioning
confidence: 99%
“…[19][20][21] There is also some evidence of a correlation with end-organ damage. [22][23][24] Observer error is eliminated and WCE is greatly reduced if measurement is performed with an observer absent, in an uninterrupted private space. Measurement is completed with 3 to 6 preprogrammed readings over 4 to 7 minutes.…”
Section: Characteristics Of Common Methods Of Bp Measurementmentioning
confidence: 99%